Workshop Seni Berbasis Pendidikan dalam Rangka Menciptakan Kreativitas untuk Pencegahan Bullying di Lingkungan Sekolah Dasar - Marmoah, Sri; Supianto, Supianto; Poerwanti, Jenny Indrastoeti; Istiyati, Siti; Sukarno, Sukarno; Mahfud, Hasan (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This service aims to increase the awareness and creativity of teachers and students regarding efforts to prevent bullying in elementary schools. The method for implementing this service used workshops and socialization in the form of FGD. This service partner was SD N 02 Nglebak, Karanganyar Regency. The data analysis technique was the stages of data reduction, data presentation, and conclusion or verification. The results of this service showed that there was an increase in awareness and creativity of teachers and students regarding the importance of preventing bullying in elementary schools. This service activity could be an effort to reduce bullying cases through knowledge about bullying prevention and teacher readiness to accompany students if bullying occurs.